PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIKPROBLEM SOLVING TERHADAP MANAJEMEN WAKTU PADA SISWA KELAS XI DI MAN 1 PATI - Atiningsih, Febri (Jurnal Psikoedukasia, 2026)
This study aims to determine the level of time management among 11th grade students at MAN 1 Pati after being given treatment in the form of group guidance services using problem-solving techniques. The method used is a quantitative approach with a pre-experimental design of the one-group pretest-posttest type. The study population consisted of 261 students, while the sample consisted of 10 students with low and high time management categories using cluster random sampling techniques. Hypothesis testing was conducted using a paired sample t-test, yielding a sig value (2-tailed) = 0.000 < 0.05, indicating a significant difference between pre-test and post-test results. The average pre-test score of 93 increased to 114.8 in the post-test, resulting in an increase of 21.8. Thus, Ho was rejected and Ha was accepted, meaning that group counseling services using problem-solving techniques significantly influenced improvements in students' time management at the 5% significance level.